THE ROLE OF ARTIFICIAL INTELLIGENCE IN MODERN MEDICAL DIAGNOSTICS - Sadulloeva Mashkhura Adizovna,; Rakhmonova Mohinur Isroilovna, (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract Artificial  intelligence  (AI)  has  become  one  of  the  most  transformative technologies  in  modern  healthcare.  Its  integration  into  medical  diagnostics  has improved accuracy, speed, and accessibility of clinical decision-making. This paper reviews the current applications of AI in diagnostic imaging, early disease detection, clinical data analysis, and personalized medicine. Challenges and future perspectives of AI-based healthcare systems are also explored.